Preparation and Characterization of Folate Modified-Chitosan Nanoparticles as New Tumor-Targeting Drug Carrier - Xing, Zhi-Hua (Asian Journal of Chemistry, 2013)
In order to enhance the tumor-targeting and anticancer activity of drugs and prolong the total duration of action, doxorubicin (DOX) -loaded foliate (FA)-decorated chitosan (CTS) nanoparticles (FA-CTS/DOX) were prepared by the ionic crosslinking method through the electrostatic interaction between the protonated amino group of chitosan in acidic conditions and the deprotonation of carboxyl group of folic acid in alkaline conditions as well as sodium tripolyphosphate (TPP). The morphological characteristics of nanoparticles were examined using transmitting electron microscope. The average particle size of nanoparticles and size distribution were determined by dynamic light scattering. The drug encapsulation efficiency, loading capacity and in vitro release characteristics were investigated using ultraviolet spectrophotometer. The results indicated that the nanoparticles are uniform spherical and regular, with a size of 145 nm, + 40 mV surface potential and good size stability. Its encapsulation efficiency and loading capacity were up to 85.9 and 14.9 %, respectively. The Higuchi equation: Q = 14.546t1/2 + 8.2579 (R2 = 0.9687) (in PBS buffer solution of pH = 7.4) can well describe release curve of the FA-CTS/DOX nanoparticles. It was inferred that the CTS-FA/DOX nanoparticles should posses good tumor targeting from the average particle size of 145 nm and the amount of folic acid conjugated with chitosan (CTS:FA = 1:17).